INTELLECTUAL CAPITAL ANALYSIS AND LEARNING ORIENTATION ON THE PERFORMANCE OF MSMES PANDAI IRON IN SUKABUMI DISTRICT - Moch Alhadi Fahtiansyah; R Deni Muhammad Danial; Nor Norisanti (Inovbiz: Jurnal Inovasi Bisnis, 2022)
MSME blacksmith is an iron carpentry business, where MSMEs are engaged in making traditional weapons, slaughter knives, kitchen knives, tajak, katana, swords and so on. This research was conducted on blacksmith SMEs in Sukabumi Regency, because there are still problems that have been found so far, namely blacksmiths processed by large companies, one of which China is able to provide cheaper prices with traditional workshops including blacksmith workshops in Sukabumi Regency. This is because China has always emphasized that cost and time are the main things in the production process. MSME blacksmiths in Sukabumi Regency generally carry out operational activities only if there is an order, which is not adjusted to the target cost, time, and quality. This study aims to determine the effect of intellectual capital and learning orientation on the performance of SMEs. The method used in this research is descriptive method and associative method with a quantitative approach. The sampling technique used by the researcher is the saturated technique, which is a number of 38 blacksmith SMEs in Sukabumi Regency. The data analysis technique used is multiple linear regression analysis which includes the coefficient of determination, multiple correlation coefficient and partial test (t test). The results of the study using the t test showed that intellectual capital (X1) had a significant effect on the performance of MSMEs (Y) and learning orientation (X2) had a significant effect on the performance of MSMEs (Y). The contribution of the influence of intellectual capital and learning orientation variables to the performance of SMEs is 91.9%. While the remaining 9.1% is influenced by other variables outside this regression equation or variables that are not examined